2019
DOI: 10.1186/s13058-019-1150-z
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase enhances chemoresistance in breast cancer through SIRT1 protein stabilization

Abstract: Background Nicotinamide N -methyltransferase (NNMT) is overexpressed in various human tumors and involved in the development and progression of several carcinomas. In breast cancer, NNMT was found to be overexpressed in several cell lines. However, the clinical relevance of NNMT in breast cancer is not yet clear. Methods NNMT expression in breast carcinoma was examined by immunohistochemistry, and then, its relationship with patient clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 29 publications
3
79
0
Order By: Relevance
“…NNMT has been recently reported to participate in the development and progression of various carcinomas and regulate cancer metabolism [12]. In breast cancer, we have found that NNMT and its product 1MNA can inhibit the mitochondrion-mediated apoptosis through decreasing intracellular ROS, which enhances the resistance to chemotherapy by SIRT1 protein stabilization [11,15]. Considering that the NNMT gene was predicted to be an autophagy regulator by genome-wide analysis [21], we investigated the role of NNMT in the autophagy of breast cancer cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…NNMT has been recently reported to participate in the development and progression of various carcinomas and regulate cancer metabolism [12]. In breast cancer, we have found that NNMT and its product 1MNA can inhibit the mitochondrion-mediated apoptosis through decreasing intracellular ROS, which enhances the resistance to chemotherapy by SIRT1 protein stabilization [11,15]. Considering that the NNMT gene was predicted to be an autophagy regulator by genome-wide analysis [21], we investigated the role of NNMT in the autophagy of breast cancer cells.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, NNMT participates in the intracellular methylation cycle, which affects the global methylation status and metabolome of cells [6]. In the past decade, NNMT was found to be highly expressed in many kinds of tumour [7][8][9][10][11] and was found to alter various cancer cell metabolism pathways to regulate the cellular stress response [12,13] and epigenetic state, which results in high expression of protumour genes [14]. In our previous study, we found that NNMT and its product 1MNA can decrease the mitochondria-mediated apoptosis by suppressing intracellular ROS in breast cancer cells [15].…”
mentioning
confidence: 99%
“…Despite an inhibitory or synergistic suppressive effect observed in the cells, in vivo confirmative observations are missing. Concerning breast cancer, EX-527 has been implicated in chemoresistance in several studies when being combined with different drugs 39 - 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that aggressive cancer cell lines have higher levels of 1-MNA because of increased NNMT activity 9 . This is supported by data showing NNMT is highly expressed in various cancers 8 , and inhibition of NNMT results in suppression of cancer progression [10][11][12][13][14][15][16] . Therefore, it is important to develop NNMT inhibitors to eradicate cancer propagation in the clinic.…”
mentioning
confidence: 58%